First‐in‐human study with SAR445088: A novel selective classical complement pathway inhibitor. Issue 4 (2nd February 2023) - Chow, Timothy; Shamszad, Pirouz; Vinnard, Christopher; Yoon, Esther; Belinski, Julia; Karpenko, Irene; Perrin, Laurent; Auwarter, Kristen; Storek, Michael; Surks, Howard; Wong, Nancy; Cohen, Yehuda Z.
Abstract: SAR445088 is an anti‐C1s humanized monoclonal antibody that inhibits activated C1s in the proximal portion of the classical complement system and has the potential to provide clinical benefit in the treatment of complement‐mediated diseases. A phase I, first‐in‐human, double‐blind, randomized, placebo‐controlled, dose‐escalation trial of single and multiple doses of SAR445088 was conducted in 93 healthy participants to evaluate the safety, tolerability, and pharmacokinetic (PK) and pharmacodynamic (PD) profiles. Single (intravenous [i.v.] and subcutaneous [s.c.]) ascending doses (SAD) and multiple (s.c.) ascending doses (MAD) of SAR445088 were well‐tolerated. The PK of SAR445088 was characterized by slow absorption after the s.c. dose and a long half‐life (mean terminal half‐life [ t 1/2 ] 8–15 weeks). Two PD assays were used to measure inhibition of the classical complement pathway (CP): Wieslab CP and complement mediated hemolytic capacity (CH50). The estimated half‐maximal inhibitory concentration (IC50 ) and 90% inhibitory concentration (IC90 ) for the Wieslab CP assay were 96.4 and 458 μg/ml, respectively, and 16.6 and 57.0 μg/ml, respectively, for the CH50 assay. In summary, SAR445088 was well‐tolerated and had favorable PK and PD profiles after SAD (i.v. or s.c.) and MAD (s.c.) in humans. These findings warrant further clinical investigations in patients with classical complement‐mediated disorders.